A stakeholder analysis of investments for wind power electricity generation in Ontario - Pejman Bahramian; Glenn P. Jenkins; Frank Milne (Queen's University, Department of Economics, 2020)
This study uses an ex-post evaluation of the grid-connected wind projects in Ontario, Canada, to quantify the stakeholder impacts of such renewable energy projects. Our study includes a financial, economic and stakeholder analysis of these wind farms. The analysis sheds light on the distributional impacts that arise when there is a significant gap between the incentives created by the financial price paid for electricity generation and the economic value of the electricity generated. The analysis shows that the negotiated power purchase agreements (PPAs) have resulted in a negative outcome for the economy in all circumstances. It is found that the present value of the economic costs is at least three times the present value of the economic benefits, including the global benefits from the reduced CO2 emissions. This loss is borne by all the stakeholders of the electricity system, except the private owners of the wind farms. The losers are primarily the electricity consumers followed by the governments. The Ontario Electricity Rebate (OER) programme, which is financed by increased government borrowing, has the effect of transferring a large share of the costs incurred to promote investments in wind power to future generations of taxpayers in Ontario.
Keywords: O55; D61; Q42; 330; economic analysis; electricity; Ontario; wind power